The crisis of kingship in late medieval Islam : Persian emigres and the making of Ottoman sovereignty - Markiewicz, Christopher, 1982- (Cambridge, United Kingdom : Cambridge University Press, 2019)
In the early sixteenth century, the political landscape of West Asia was completely transformed: of the previous four major powers, only one - the Ottoman Empire - continued to exist. Ottoman survival was, in part, predicated on transition to a new mode of kingship, enabling its transformation from regional dynastic sultanate to empire of global stature. In this book, Christopher Markiewicz uses as a departure point the life and thought of Idris Bidlisi (1457-1520), one of the most dynamic scholars and statesmen of the period. Through this examination, he highlights the series of ideological and administrative crises in the fifteenth-century sultanates of Islamic lands that gave rise to this new conception of kingship and became the basis for sovereign authority not only within the Ottoman Empire but also across other Muslim empires in the early modern period.
The realm of generation and decay : Bidlisi in Iran, 1457-1502 -- Patronage and place among the Ottomans : Bidlisi and the Court of Bayezid II, 1502-1511 -- The return east (1511-1520) -- The Timurid vocabulary of sovereignty -- The canons of conventional histories -- Ottoman sovereignty on the cusp of universal empire.
Includes bibliographical references [pages 305-334] and index.
Keywords: Monarchy -- Turkey; Turkey -- Politics and government; Political science -- Turkey -- History -- 16th century; Idris Bitlisi, -- -1520.; Sovereignty